Calm the f*ck down how to control what you can and accept what you can't so you can stop freaking out and get on with your life - Knight, Sarah (Freelance editor) (London Quercusy, 2018)
"Outlines a customizable "emotional insurance" plan for navigating life's inevitable setbacks, sharing irreverent advice for calming anxiety and moving forward. Do you spend more time worrying about problems than solving them? Do you let unexpected difficulties ruin your day and do "what ifs" keep you up at night? Sounds like you need to CALM THE F*CK DOWN. Just because things are falling apart doesn't mean YOU can't pull it together. Whether you're stressed about sh*t that hasn't happened yet or freaked out about sh*t that already has, the NoWorries method from "anti-guru" Sarah Knight helps you curb the anxiety and overthinking that's making everything worse. Calm the F*ck Down explains: The Four Faces of Freaking Out--and their Flipsides, How to accept what you can't control, Productive Helpful Effective Worrying (PHEW), The Three Principles of Dealing With It, and much more!" --
"The no-f*cks-given guide to taming anxiety and taking control of your life. Do you spend more time worrying about problems than solving them? Do you let unexpected difficulties ruin your day and do 'what ifs' keep you up at night? Sounds like you need to CALM THE F*CK DOWN. Just because things are falling apart doesn't mean YOU can't pull it together. Whether you're stressed about sh*t that hasn't happened yet or freaked out about sh*t that already has, the NoWorries method from 'anti-guru' Sarah Knight helps you curb the anxiety and overthinking that's making everything worse. Calm the F*ck Down explains: the Four Faces of Freaking Out--and their Flipsides; how to accept what you can't control; Productive Helpful Effective Worrying (PHEW); the Three Principles of Dealing With It; and much more!"--Back cover
Introduction -- So you're freaking out : acknowledge the real problem and rein in your reaction -- Calm the fuck down : identify what you can control, accept what you can't, and let that shit go -- Deal with it : address what you can control -- Choose your own adventure : when shit happens, how will you calm the fuck down and deal with it?
An asterisk is used to substitute the U in "fuck"
Includes index
1
Keywords: Anxiety; Anxiety; Calmness; Calmness; Conduct of life; Conduct of life; Life skills; Life skills; SELF-HELP / Motivational & Inspirational; SELF-HELP / Personal Growth / Happiness; SELF-HELP / Self-Management / Stress Management; Self-help techniques; Self-help techniques; Calmness; Anxiety; Calmness; Conduct of life; Fear; Life skills; SELF-HELP / Motivational & Inspirational; SELF-HELP / Personal Growth / Happiness; SELF-HELP / Self-Management / Stress Management; Self-help techniques; Worry